„Poezje są jak świątyń barwne szyby!” - Pastwa, Rafał Jakub (Poznańskie Studia Polonistyczne. Seria Literacka, 2023)
The readers of Rozalia Wojkiewicz’s book W spektrum Wyspiańskiego. Witraż w poezji Młodej Polski (In Wyspiański’s spectrum. Stained glass windows in Young Poland Poetry) are presented with a unique study of Stanisław Wyspiański, his work, his journey along the trail of “barbaric” cathedrals, his passion and aspirations, the spirit of the era and, above all, an analysis of stained glass – a special type of text reflected not only in poetry and one which grew out of man’s aspirations to understand what is hidden, created, fragile and at the same time incomprehensible. The analysis conducted by Rozalia Wojkiewicz serves as a gradual, planned entry into the world of the Young Poland stained glass collection, explains the reasons for the interest in the subject, and presents the valuable state of research on it and the method of its observation.